Flipped learning liikunnan opetuksessa: liikunnanopettajien kokemuksia menetelmästä - Kuningas, Laura (2025)
Kuningas, L. 2025. Flipped learning in physical education: physical education teachers' experiences of the method. University of Jyväskylä, Sport Pedagogy, master’s thesis, 42 pages, 1 appendice.